Вескость слов и сила молчания в ненецких рассказах о жизни/The Weight of Words and the Power of Silence in the Nenets Life Story Narratives - Laptander, Roza (Научный вестник Ямало-Ненецкого автономного округа, 2021)
By the example of Nenets oral stories, this article describes the features of transmission, memorization and narration of oral stories about the past, and the role of silence in narration. They contribute to the preservation or loss of memories of the past. The results of the study described the norms of preservation of Nenets individual and collective memories of the past, in which the culture of silence can have particular importance. It was found that selective narration of stories about the past contributes to the formation of a positive perception of ethnic history among the younger generation of Nenets. At the same time, in the Nenets culture, silence has a special role and significance, which was developed under the influence of religious norms of behavior, social relations and cohabitation on a common territory of the Yamal Peninsula. The Nenets stories tell about the events that took place in Yamal from the beginning of the 19th century to the present time. These forms of narration of spoken stories are common not only for the Nenets but also for other peoples of the former Soviet Union and the indigenous peoples of the Arctic. Together they illustrate the role of responsibility, demands and interests of society in the formation of individual and common, collective memories of the past.